A synthesis of early and middle Holocene coastal changes in the western Belgian lowlands - Cecile Baeteman; Pierre-Yves Declercq (Belgeo)
A large-scale pattern of Holocene coastal evolution of the western Belgian coastal plain has been reconstructed by means of a series of palaeogeographical maps at 9 time slices between 9.5 and 6 cal. ka BP together with schematical cross-sections of the vertical sediment accumulation. The time-depth estimate and the spatial extension of the palaeo-environments is based on the relative sea-level (RSL) curve and radiocarbon dates of (basal and intercalated) peats and shells. This paper describes the methodology of reconstructing the pre-Holocene surface and asserts that the morphology of the flooded surface is a controlling factor in the distribution of the Holocene sediments. For a better visualization of the rather weak relief, a 3D terrain model is presented. The coastal evolution is further controlled by the changes in the rate of RSL rise and sediment budget. The period before ca. 7.500 cal BP is marked by a rapid RSL rise and consequently by a progressive rapid landward migration of all depositional environments as well as a major vertical sediment accretion. In the period following the first substantial decrease in the rate of RSL rise, the direct impact of the latter is subordinate to the effect of sediment budget which is in balance with the creation of accommodation space. This resulted in the sedimentary infilling of the tidal basin and the deposition of tidal clastic sediments with peat accumulation.